11 Quality analysis of cranio-spinal RT treatments (CSI) in helical Tomotherapy (HT) and protontherapy at the Institut Curie. (December 2018) - Dartiguemalle, M.; Caneva-Losa, S.; Amessis, M.; Alapetite, C.; Pierrat, N.
Abstract : Introduction: Since 2010, about fifty patients have been treated with CSI in HT (Accuray) with a photon or proton boost depending on the indication. This population is the subject of an analysis of the quality of treatment plans. Since the installation of dynamic jaws (TomoEdge, 2014) and TPS updates (Volo), we have modified our clinical protocols to optimize treatments. The objectives and constraints of brain PTV and nevrax PTV volumes, ±boost PTV, and OARS are based on our clinical experience (SIOP group: brain tumors). Quality indices (IQ) such as the homogeneity index HI (optimal value zero) and the conformity index: Target Coverage TCO (optimal value 100%) are determined. Methods: All patient data were collected and sorted according to their medical prescription in MS Excel. The QI are obtained by exporting the TPS treatment plans to the Artiview software (Aquilab, France) in DICOM format. The representation of dosimetric data on Artiview has been fully validated, notably on dosimetric indicators such as average dose, maximum dose, minimum dose, QI, D95%, computing grid, etc…The feasibility of this project was then performed on a sample of ten patients treated in 36 Gy (1.8 Gy/fraction) without boost. Results: We observe an evolution in the clinical protocols implemented, particularly in the choice of collimator settings (2.5 cm to 5 cm), pitch and modulation factor, with a significant reduction in treatment time (35 min to 10 min), while maintaining PTV coverage and the constraints imposed on OAR. The relative differences between TPS and Artiview dosimetric indicators are less than 1.3%. For PTV: Brain PTV: Dmean = 36.3 Gy, D95% = 34.3 Gy, HI = 0.125 (0.056–0.502) and TCO = 97.3% (87.6%–99.8%). PTV nevrax: Dmean = 36.4 Gy, D95% = 34.8 Gy, HI = 0.095 (0.061–0.211) and TCO = 97.1% (82.1%–99.9%). For OAR: Eye: Dmean = 13.9 Gy. Crystallin: Dmax = 7.8 Gy. Oral cavity: Dmean = 9.6 Gy. Thyroid: Dmean = 12.9 Gy. Lungs: Dmean = 6.6 Gy, V20Gy = 6.4%. Heart: Dmean = 11.1 Gy. Liver: Dmean = 7.0 Gy. Kidneys: Dmean = 4.7 Gy, V12Gy = 5.8%. Ovaries: Dmax = 1 Gy. Testicles: Dmax = 0.2 Gy. Conclusions: We validated the feasibility of the whole process. The complete study will cover the entire population according to therapeutic indications. The modification of the QI is under evaluation for a better representation of the data. Finally, a comparison with conformational and/or proton treatments can also be made.